Bibliometric insights into HRM and innovative work behavior nexus: tracing past, present and future developments - Wider, Walton; Lin, Jiaming; Muhammad Ashraf, Fauzi (Emerald Publisher, 2024)
Purpose: The capacity of organizations to adapt swiftly and implement innovative approaches has ignited discussions about which human resource management (HRM) practices can foster creativity and innovative work behavior (IWB) among employees. Research suggests that IWB thrives in an environment where HRM acts as the architect, influencer and developer. However, our understanding of the specific HRM practices that promote innovative work behaviors remains limited. Existing studies offer scattered and occasionally conflicting insights, particularly concerning measurements and theoretical frameworks that could enable greater generalizability. Consequently, a comprehensive review of the relationships between HRM, innovation and IWB could provide clearer evidence about how HRM impacts innovation. This research presents a bibliometric analysis of research on the relationship between HRM and IWB. The purpose of this analysis is to provide an in-depth overview of the current state and future prospects of HRM and IWB by examining past and current research trends and predict future research directions. Design/methodology/approach: The study used a bibliometric approach to collect 280 journal articles from the Web of Science database. The study identifies the most influential publications, outlines the knowledge structure and forecasts future trends using co-citation and co-word analysis. Findings: The results of the co-citation and co-word analysis revealed the existence of four clusters. While acknowledging some limitations, this review sheds light on the expanding field of HRM and IWB research. Practical implications: The study provides a comprehensive understanding of HRM and IWB as well as insights into future advancements in the field. Originality/value: This is the first study to use bibliometric analysis based on the Web of Science (WOS) database to conduct a quantitative evaluation of the HRM practice and IWB literature.